PENYELESAIAN WANPRESTASI PEMASANGAN KWH METER PT. RTU DAN MASYARAKAT DESA KEPENGHULUAN KOTA PARET KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - William Joshua Sinaga; Zulfikar Jayakusuma; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Electricity is the object of the transaction for the installation of the installation which contains a large enough risk. In the installation of electrical installations from PLN, an agreement must be made between the electricity customer and the company. This incident creates a relationship between the two people which is called an engagement. However, in reality there are still many accomplishments that have not been carried out, causing default. For example, the problem in Kepenghuluan Village, Rokan Hilir Regency, where their right to get an electricity installation until it turns on is not fulfilled because of the negligence of the company, namely PT. RTU that causes default.The purpose of this research is to find out about the implementation of cooperation as well as the rights and obligations of PT.RTU and the community as parties that bind themselves to the agreement, to find out the obstacles in implementing the agreement and to find out how to solve them that arise in the agreement process. The type of legal research the writer uses is sociological research. This sociological legal research is a type of research that is viewed from the purpose of legal research. Sociological or empirical legal research consists of legal identification (unwritten) and research on the effectiveness of the lawIn the results of research and discussion there are 3 main problems that can be concluded. First, the party that binds itself to the agreement has rights and obligations that must be fulfilled, namely the first party as the people of Kepenghuluam Village has the right to get an electricity installation until it turns on, and the second party who has the obligation to complete the work of installing electrical installations in Kepenghuluan Village to electricity in the village can light up. Second, an unfulfilled achievement is called a default, namely the incomplete installation of the electrical installation causes losses to one of the parties and can be held accountable. Third, the form of responsibility can be in the form of fulfilling achievements or compensation, namely completing the installation of electrical installations or returning the money that has been depositedKeyword: Agreement, Default, Dispute Resolution